Evaluation Of Selected sankhupushpam (Clitoria ternatea L.) Lines For Yield ,Alkaloid Content And Nodulation - Reshmi CR (Department of Plantation crops and spices, College of Horticulture, 2001)
The present study entitled 'Evaluation of selected Sankhupushpam (Clitoria ternatea L.) lines for yield, alkaloid content and nodulation' was carried out at the Department of Plantation Crops and Spices, College of Agriculture, Vellayani from June to December 2000. Six superior lines evolved from a preliminary screening of genetic stock conducted by Nair (2000) were raised under shade, as an intercrop in coconut garden and in open as a pure crop. Various biometric observations were taken at four different stages of plant growth, viz., pre-flowering (45 DAS), flowering (90 DAS), seed formation (135 DAS) and seed maturation (180 DAS) stages. These included observations on shoot yield, root yield and pod yield. Nodule characteristics were also recorded. Phytochemical analysis was carried out after harvest of the crop to estimate the crude alkaloid content in the seeds of each accession. Analysis of the results revealed maximum shoot yield for MP-73 and MP-8I under shade and open conditions respectively. The highest pod yield was recorded for MP-76 under shade and for MP-73 under open condition. Root yield on fresh weight basis was found to be the highest for MP-76 under shade and MP-74 under open condition. On dry weight basis, root yield was maximum for MP-74 under shade and for MP-8I under open condition. Maximum nodulation at flowering stage was observed in MP-73 and MP-7& under shade and open conditions respectively. MP-73 and MP-76